Combined effects of dietary mannan oligosaccharides and total fish oil substitution by soybean oil on European sea bass (Dicentrarchus labrax) juvenile diets. (16th May 2015) - Torrecillas, S.; Caballero, M.J.; Montero, D.; Sweetman, J.; Izquierdo, M.
Abstract: This study evaluates the effects of dietary mannan oligosaccharides (MOS) on growth, tissue composition, fatty acid profiles and liver morphology of European sea bass ( Dicentrarchus labrax ) fed diets containing either soybean oil (SBO; SBOMOS) or fish oil (FO; FOMOS) as unique oil source for 8 weeks. Results showed that MOS supplementation enhanced specific growth rate, regardless of the oil source used, and that dietary oil source reduced fish length, regardless of dietary MOS supplementation. Dietary MOS favoured lipid accumulation in muscle and anterior intestine when supplemented in FO‐based diets compared to fish fed SBO diet and reduces it in liver in relation to lower hepatocyte area, particularly in fish fed SBOMOS diet. Dietary MOS favoured liver and not muscular ∑n‐3 PUFA, DHA, EPA and ARA deposition, when combined with FO but not when included in SBO‐based diets. Thus, MOS dietary supplementation favours fish performance and helps to minimize the side effects derived from high dietary SBO supplementation on liver lipid accumulation and hepatocyte vacuolization, which could be of especial interest on long‐term feeding trials; however, the effects on favoured deposition ∑n‐3 PUFA are limited to FO‐based diets.